Pharmacovigilance: An Essential Tool for Drug Safety Monitoring - JasmineJinitha, A; Rexline, SJ (International Journal of Computer Sciences and Engineering, 2025)
Pharmacovigilance(PV) is the science and activities relating to the detection , assessment, understanding and prevention of adverse effects. Adverse effects means the abnormal conditions occurs in the body due to the drugs which are consumed by the peoples. The main process of pharmacovigilance is reporting about the safety and quality of the drugs. It makes the treatment for patients as worthy as possible. This process makes the subject of chemical compositions of the drugs worthy and correctly. This is one of the major process in drug industries. The proposed system use an ideal tool for this process is the reporting by means of forms which are available under medical bodies also by means of web applications for pharmacovigilance process. This paper presents the better results in clinical trials. The success or failure of pharmacovigilance activity depends on the reporting of suspected adverse reactions. Reports made by a health professional are an interpretation of information originally provided by a patient who has experienced the actual benefit or harm of a medicine taken.